(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to identify the challenges facing accounting education in light of the widespread use of Artificial Intelligence (AI) and to explore ways to overcome these challenges from the perspective of postgraduate students in the Accounting Department in the Western Region. To achieve this objective, the descriptive analytical approach was adopted. An electronic questionnaire was randomly distributed to the study population, and a total of (50) responses were collected. The study revealed several important findings, most notably that accounting education faces significant challenges in the era of artificial intelligence. These challenges include reliance on traditional teaching methods, limited financial and technological resources, and the lack of experience among faculty members. The results also indicated a clear shortcoming in the role of the Ministry of Education in addressing these issues. The study recommended several measures, the most important of which are the development of accounting education through the integration of artificial intelligence technologies into the educational process, the provision of financial and technological support to educational institutions, and the qualification of academic staff. It also recommended updating accounting curricula and establishing the necessary regulations in line with the requirements of digital transformation.